The Cardiovascular Diseases Risk among the Akha Ethnic Group in Mae Suai District, Chiang Rai Province - Suthipong, Chittraphorn; Srimantayamas, Vipada; Boonyapuk, Pimrat (Journal of The Royal Thai Army Nurses, 2024)
Cardiovascular diseases present a significant health challenge within the Akha ethnic community. This prospective observational study seeks to evaluate the risk factors for cardiovascular diseases over the next ten years among the Akha population in the Mae Suai district, Chiang Rai province. Employing a simple random sampling method, 128 individuals were included in the study. The research utilized various tools, including personal data records, assessments of disease risk factors, Stress Test 5 (ST5) evaluations, and the Thai CV risk score application from Ramathibodi Hospital’s Faculty of Medicine.The statistical analysis encompassed both descriptive and inferential methods, investigating the relationships between disease occurrence and various risk factors. Findings indicated that 77.30% of the Akha ethnic group faced the risk of cardiovascular diseases over the next ten years, with 15.60% in the moderate risk category and 7.00% at high risk. Notably, individuals with hypertension exhibited a 3.48 times higher risk of developing cardiovascular diseases compared to other the risk of cardiovascular diseases over the next ten years. To proactively address the risk of cardiovascular diseases over the next ten years, health promotion initiatives should concentrate on heightening awareness about blood pressure control, proper nutrition, stress reduction, regular exercise, and smoking cessation among individuals in the Akha ethnic group. These targeted efforts aim to empower the community with knowledge and preventive strategies, fostering a healthier cardiovascular profile for the Akha population in the years to come.